Potential impact and mechanism of aged polyethylene microplastics on nitrogen assimilation of Lactuca sativa L. - Xiaoli Mou; Hedong Zhu; Renrui Dai; Li Lu; Shengqi Qi; Min Zhu; Yuyang Long; Nan Ma; Chao Chen; Jiali Shentu (Ecotoxicology and Environmental Safety)
Nitrogen (N) is the driving factor for crop yield and quality, and more research is needed on the mechanisms of aged micro/nano plastics (MNPs) on N assimilation in edible crops. In this study, pot experiments were conducted to investigate the potential effect of aged polyethylene (PE) microplastic addition (particle sizes: 20 and 0.1 µm, addition levels: 0.5 % [w/w], referred to as the control (CK), P20 (20-µm PE), AP20 (20-µm aged PE), P0.1 (0.1-µm PE), AP0.1 (0.1-µm aged PE) on MNPs accumulation and N assimilation in romaine lettuce (Lactuca sativa L.). The results showed that the particle size of MNPs accumulated in lettuce decreased from root > stem > leaf. Compared to CK, the fresh plant weight significantly decreased by 40.84 and 51.62 % in AP20 and AP0.1, respectively. The results indicated that MNPs could affect lettuce growth via soil nutrient availability, and aged 100-nm PE decreased soil NH4+ and plant TN concentrations by 9.10 and 21.99 %, respectively, compared to that in CK. N assimilation in lettuce was significantly inhibited by aged MNPs, which manifested as the soluble protein content in lettuce under AP20 and AP0.1 treatments being significantly reduced by 30.59 and 42.11 %, respectively (P < 0.01). Possible mechanisms included inhibition of carbon assimilation, photosynthesis, and Ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco). The toxic effect of aged MNPs on growth and N assimilation in lettuce was much greater than that of the particle size, which was attributed to the carbonyl and hydroxyl groups caused by aging. Structural equation modeling showed that soil nitrogen positively affected total nitrogen (TN) (0.359), chlorophyll (0.665), Rubisco (0.441), soluble protein (0.383), and biomass (0.460), and negatively affected phosphoenolpyruvate carboxylase (PEPC) (-0.325), soluble sugar (-0.134). This study enhances current understandings of the effects of microplastics on N assimilation in edible crops. The findings indicated that aged MNPs accumulation in vegetables may negatively affect agricultural sustainability and food safety.